2016
DOI: 10.1016/j.watres.2015.12.047
|View full text |Cite
|
Sign up to set email alerts
|

Fingerprinting the reactive toxicity pathways of 50 drinking water disinfection by-products

Abstract: A set of nine in vitro cellular bioassays indicative of different stages of the cellular toxicity pathway was applied to 50 disinfection by-products (DBPs) to obtain a better understanding of the commonalities and differences in the molecular mechanisms of reactive toxicity of DBPs. An Eschericia coli test battery revealed reactivity towards proteins/peptides for 64% of the compounds. 98% activated the NRf2-mediated oxidative stress response and 68% induced an adaptive stress response to genotoxic effects as i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
147
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 167 publications
(159 citation statements)
references
References 70 publications
4
147
0
Order By: Relevance
“…However, the formation of hazardous disinfection by-products (DBPs), such as trihalomethanes, haloacetic acids, nitrosamines, cyanogen halides, haloacetonitriles (HANs), haloacetamides, halonitromethanes and so on, through reactions between precursor materials and chlorine has been reported (Ma et al, 2014;Muellner et al, 2007;Stalter et al, 2016;West et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…However, the formation of hazardous disinfection by-products (DBPs), such as trihalomethanes, haloacetic acids, nitrosamines, cyanogen halides, haloacetonitriles (HANs), haloacetamides, halonitromethanes and so on, through reactions between precursor materials and chlorine has been reported (Ma et al, 2014;Muellner et al, 2007;Stalter et al, 2016;West et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…That study also compared 26 carbon-based DBPs and 29 nitrogenous DBPs (N-DBPs) and found that N-DBPs are the most toxic among all DBPs investigated. These trends were also consistent with the recent study by Stalter et al (2016a) wherein a set of cell-based in vitro bioassays was used to assess molecular mechanisms of reactive toxicity of 50 different DBP species.…”
Section: Bioassays For Dbp Studiessupporting
confidence: 89%
“…Although N-DBP concentrations are lower than C-DBPs, increasing concerns on N-DBP formation arise because of its higher toxicity compared to C-DBPs (Plewa et al 2008, Stalter et al 2016a). Halonitromethanes (HNMs), haloacetonitriles (HANs), and haloacetamides (HAMs) are among the most frequently detected N-DBPs in drinking water.…”
Section: Nitrogenous Dbp Formationmentioning
confidence: 99%
See 2 more Smart Citations